Tropospheric structure and jet-streams over the Middle-East in winter - SINGH, M. S. (MAUSAM, 1980)
Jet-streams and some aspects of the upper atmospheric structure over the Middle-East have been studied with the help of January data of four years, i.e., 1975-1978. It was found that there are, in general, two jet cores along 45 deg. E to 50 deg. E south of 45 deg. N, one at 31 deg. N at an altitude of 190 mb with core speed of 175 kt and the other at 25 deg. N at an altitude of 220 mb and core speed of 150 kt. They are subtropical in nature and are located along and above a subtropical front which is well developed. There is no other jet-core between 31 deg. N and 45 deg. N indicating that the atmosphere in this region is apparently dominated by the tropical/subtropical airmass in winter.